Perspectives on “Good” in Blockchain for Good - Parry, Glenn; Collomosse, John (Frontiers in Blockchain, 2021)
Blockchain projects have been developed to extend the reach of Distributed Ledger Technology (DLT) beyond cryptocurrency to achieve ‘good’ in the world. Such projects may make a claim for moral, ethical, and responsible intent, but many researchers have not critically examined what good means in context. The concept of good has been debated for centuries and whilst we will not conclude the argument, we should engage in the discourse. We propose that exploration across micro, meso and macro levels of value creating ecosystems is needed. The implications, both practical and theoretical, of the use of blockchain for good requires analysis. As the ambition for Blockchain innovations to transform society for the better becomes practical reality, understanding of such change will come from transdisciplinary researchers able to bridge knowledge of social and technical systems.